DYNIC PARADIGM ON METAMORPHOSIS REPRODUCTION (METAMOREP) THEORY IN 6 TIMES AS QURAN AND UNIVERSE IN ECONOMIC COVID ERA - R Mochamad A (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study is to analyze the creation of the universe with the Islamic Dynik Paradigm according to the Quran and the R12 Metamorep Theory in the 6 stages of the Covid economic era. The theory of R12 Metamorep is based on the formula R12 and the pattern of metamorphosis and reproduction period. R12 is the Roikhan-12 formula that develops the Initial Edge Concept. The Metamorphosis Pattern is found in the changes in the Butterfly from the beginning. The reproductive period occurs when there is a developing reproductive system. The Dynik paradigm refers to the content of scriptures according to truth and facts. This research was conducted in a desk study by collecting sources from scriptures, journals, books, and electronic media. The methodology used is Reflective Qualitative. The method used is metaphor and similarity. The results obtained are the Theory of Reproductive Metamorphosis R12 in the creation of the universe consisting of 6 stages. This stage is a combination of the butterfly life cycle plus the creature's breeding cycle according to the Quran Surah An-Naziat [97: 27-33. It starts with a dot-like egg that contains a high density of matter. Then there is a separation in the form of the Initial Edge Concept. The Dynik paradigm from QS 3.19 that every creation has an Islamic meaning will be a solution for the development of the theory of the creation of the universe that combines existing theory with the contents of the holy book of the Covid economic era.Keywords: Paradigm, Dynik, Metamorphic, Metamorphosis, Reproduction